Hispanism in Czechoslovakia - Montoro Cano, del Rocio Estela (Romanica Olomucensia, 2014)
This work is focused on the scientific production of Hispanists (translators, linguists and scholars), prominent personalities in the early studies of the language and literature of Spanish-speaking countries in the ancient Czechoslovakia, being authors of monographs, manuals, dictionaries, papers and texts for students in different specialized magazines and journals, published not only in their own country but also abroad.
Keywords: Spanish language; Czechoslovakia; Spanish and Latin America literature; historiography; lexicography.